#Closethegap accelerate post-pandemic recovery through social justice. (PIDS 2021-2022 Economic Policy Monitor, 2022)
This issue of the Economic Policy Monitor (EPM) highlights the disproportionate impacts of the COVID-19 pandemic on the country’s marginalized and vulnerable sectors. It analyzes the role of social justice in fast-tracking the Philippines’ post-pandemic recovery and how social justice can help minimize deep-seated socioeconomic inequalities exacerbated by the pandemic. This EPM likewise reviews the Philippines’ macroeconomic performance in 2021 and presents economic projections for 2022 and 2023. Moreover, it provides policy memos to guide the new administration in addressing pressing issues in health, education, social protection, social mobility, overseas Filipino workers, housing, labor and employment, information and communications technology, innovation, agriculture, environment and natural resources, trade and industry, services, energy, air and water transport and public sector investments.$bback cover